Beach Cleaner Crab Machine - Mohammad Noor, Hafsa; Muhamad Amir Aiman Mohd Karim; Ahmad Syahidi Rosli; Muhamad Harith Sufian Mohd Zulkifli (Multidisciplinary Applied Research and Innovation, 2023)
In Malaysia, the problem of pollution at the beach is there are some plastics, bottles, and similar to that where the visitors commonly leave their food, drinks, and other waste everywhere which makes the place a bad view to others. All of this trash, plastic trash has the greatest potential to harm the environment, wildlife, and humans. It can be found floating at the surface, suspended in the water column, or on the bottom of almost all water bodies. It is transported by rivers to the ocean, where it moves with the currents, and is often eaten by birds and fish, concentrating toxic chemicals in their tissues, and filling their stomachs, causing them to starve. Beach Cleaner Crab machine was fabricated to speed up the time in collecting the rubbish at the beach by using excavator arm technology which manages to lift up to 1kg of rubbish per arm. In addition, it may reduce the rate of garbage pollution at the beach in Malaysia. Otherwise, it is designed to be a friendly machine which is it can be controlled at any age. Moreover, this Machine used the gear system at the front tire. This is because this machine is operated by using manual techniques and is more environmentally friendly. Last but not least, results showed that Beach Cleaner Crab requires 80 % less time and energy than a manual pick-up.